Risk Analysis Of Occupational Safety And Health In Core Wall Construction Work At A Communication Tower Project - Laksmi, Kadek Kristina Fajar; Dewi, Ratna Sari (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze Occupational Health and Safety (OHS) risks in the core wall construction work of the Communication Tower Project, which has reached 70% progress. Over 80% of the work is carried out by vendors and subcontractors, presenting challenges in coordination and standardization of OHS practices. The methods employed include Job Safety Analysis (JSA), Hazard Identification, Risk Assessment, and Determining Control (HIRADC), Analytical Hierarchy Process (AHP), and Cost-Benefit Analysis (CBA). Data were collected through field observations, questionnaires, and interviews with fifteen respondents ranging from field workers to project managers. The results show that the highest-risk activities are climbing formwork and reforming roof, both classified as high-risk. AHP was used to prioritize mitigation actions based on three criteria: severity, likelihood, and cost, with severity identified as the most dominant factor. CBA indicated that despite the relatively high mitigation costs, the proposed controls are effective in significantly reducing risk exposure, especially for activities at height and heavy equipment operation. The integration of these four methods provides a mitigation strategy that is data-driven, cost-efficient, and applicable to large-scale and complex construction projects.